Interaction of Riwayah and Dirayah Science in Learning Hadith - Tarmizi M. Jakfar (Sharia and Law Faculty, 2022)
This article attempts to explain the pattern of interaction between history and dirayah in learning hadith. So far, hadith science tends to be classified into two types, namely riwayah hadith science and dirayah hadith science. In fact, in its development, these two types of hadith science interact with each other. Therefore, the focus of this study is to discuss how the interaction between the science of hadith history and the science of hadith is explored in learning hadith? The method used is qualitative by using data from the hadith books used by the scholars. The results of the study show that the science of riwayah hadith has a very close relationship with the science of hadith dirayah. Because the quality of riwayah hadith science is only known through research on the sanad of the hadith, while the sanad is the object of dirayah hadith science. In addition, the science of hadith riwayah only focuses on the narration as it is from the Prophet while the science of hadith dirayah discusses how to understand the material of the history. The science of hadith history is like the Koran, while the science of hadith is like interpretation of it, one cannot understand the Koran without knowing its meaning or interpretation. This is the interaction between these two fields of science that cannot be separated from one another. By integrating these two branches of knowledge, learning the science of hadith will be more useful as a second source of teachings in Islam. Artikel ini berusahan menjelaskan pola interaksi antara ilmu riwayah dan dirayah dalam pembelajaran hadis. Selama ini, ilmu hadis cenderung diklasifikasikan kepada dua jenis, yaitu ilmu hadis riwayah dan ilmu hadis dirayah. Padahal, dalam perkembangannya, kedua jenis ilmu hadis ini saling berintaeraksi satu sama lain. Oleh karena itu, fokus kajian ini membahas bagaimana interaksi antara ilmu hadis riwayah dan ilmu hadis dirayah dalam pembelajaran hadis? Adapun metode yang digunakan adalah kualitatif dengan menggunakan data dari kitab-kitab hadis yang digunakan oleh para ulama. Hasil penelitian menunjukkan bahwa ilmu hadis riwayah mempunyai hubungan yang sangat erat dengan ilmu hadis dirayah. Karena kualitas ilmu hadis riwayah hanya diketahui melalui penelitian terhadap sanad dari hadis tersebut, sementara sanad itu adalah objek dari ilmu hadis dirayah. Selain itu, ilmu hadis riwayah hanya fokus kepada periwayatan apa adanya dari Nabi sementara ilmu hadis dirayah membahas bagaimana memahami materi riwayat tersebut. Ilmu hadis riwayah ibarat al-Qur’an, sementara ilmu hadis dirayah ibarat penafsiran terhadapnya, tidak bisa memahami al-Qur’an tanpa mengetahui makna atau penafsirannya. Inilah interaksi antara dua bidang ilmu ini yang tidak bisa dipisahkan antara satu dan lainnya. Dengan memadukan kedua cabang ilmu ini maka pembelajaran ilmu hadis akan lebih berguna sebagai sumber ajaran yang kedua dalam Islam.